Fintech and healthtech synergism: Pioneering a digital healthcare revolution for accessible, affordable, and effective patient-centered care - Rushikesh Shukla; Harshit Bagotia; Poorvikha Satish; H Shruthi Kamath; Swastika Chatterjee; Donald Savariah; Ved Kaulgud; Harsha Gobburi; Sourya Acharya (Journal of Family Medicine and Primary Care)
The blending of financial technology (fintech) and health technology (healthtech) has the potential to bring about major changes in the healthcare industry. In this review, we have delved into this convergence and explored how it can improve healthcare access, affordability, and patient outcomes. Beginning with a delineation of fintech and healthtech, we analyzed the impact of financial innovations such as mobile payment systems, crowdfunding platforms, and blockchain technology on healthcare. Additionally, we examined the rising trends in healthtech integration, such as telemedicine, wearable devices, and health data analytics, and how these technologies intersect with financial systems to enhance healthcare delivery. By showcasing real-life examples and case studies, the study demonstrated how fintech and healthtech solutions have been successfully implemented in healthcare settings. But why doesn’t everyone take them up? Regulatory complexities along with ethical considerations are two of the main barriers toward large-scale adoption of these solutions, besides technological limitations. It is crucial to meet these challenges if financial and healthcare solutions are going to be successfully combined through continued innovation.